Launching the Newfoundland and Labrador Health Research Ethics Authority Act and Reflections on its Current Status - Moody-Corbett, Penny; Buehler, Sharon (Canadian Journal of Bioethics / Revue canadienne de bioéthique)

(untitled) (Programmes de bioéthique, École de santé publique de l'Université de Montréal, 2022)
The Health Research Ethics Authority (HREA) Act was established to ensure that research ethics review of all human health research in the province of Newfoundland and Labrador is conducted by a local, in-province, Research Ethics Board (REB). The HREA Act arose as a result of complaints by patients and family members enrolled in a clinical genetics research study being conducted by a team of researchers from outside the province who failed to provide appropriate clinical follow-up. This review provides a record of the steps taken to draft the legislation and prepare for proclamation and includes information on the key stakeholders involved in the process. The review also provides a brief commentary on the HREA, and the newly formed Health Research Ethics Board, in the years following proclamation and how the HREA aligns with national interests for harmonizing research ethics review across multiple REBs. At the outset, the process was envisioned as simply moving to a provincially legislated research ethics board; however, the actual task involved establishing a new entity to oversee research ethics review and expanding or enhancing the office required to manage this research ethics review oversight. The task for the working committees involved in establishing the legislation was more complex than envisioned by the partner organizations, the government of Newfoundland and Labrador, Memorial University of Newfoundland and the Eastern Health Authority, and the workload and time to establish and proclaim the legislation was more involved than anticipated.